Pemanfaatan E-Commerce Go Mart Dalam Pemasaran UMKM Di Kota Medan - Siti Aisyah; Indah Mutiara Ayu; Nila Rosdiana; Dona Zahra Hasibuan; Rediansyah Saranan (Institut Teknologi dan Bisnis Semarang, 2023)
This PKM is an activity that has a role in carrying out useful service to the community. The main purpose of this PKM activity is to provide insight to the public regarding the use of Go Mart e-commerce as an effort to improve marketing for UMKM Ayah Shops in Medan City. This PKM activity is expected to provide marketing opportunities for the owner of Ayah's Shop to increase sales volume with the help of Go Mart e-commerce. The approach used in this activity was qualitative with the methods used to collect data in the form of group discussions, documentation, biographies to interviews as well as observation and content analysis. In this activity, the researcher provides directions for the owner of Ayah's Shop to take several steps as a marketing medium through the Go-Mart. The existence of Go-Mart as a shopping application platform that is efficient and easy to use. In practice. The marketing process carried out with the Go-Mart application goes through several stages so that Toko Ayah's products can be recognized by a wide range of people through postings on e-commerce and can increase the quantity of service to consumers.